Pertanggung Jawaban Notaris terhadap Akta Otentik Yang Dibuat Dihadapannya : Studi Kasus Putusan Nomor 247/Pdt.G/2021/PN Ckr - Dodi Sudirman; Maman Suparman (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
Notaries in carrying out their duties and responsibilities are required to always apply the precautionary principle. This is intended so that notaries can provide the best service to the public. Apart from that, notaries who do not apply the precautionary principle may be subject to sanctions. The large number of notaries makes competition between notaries increasingly fierce and sometimes makes notaries less careful in carrying out their profession. Therefore, the emergence of this short article is an attempt to review the main issue, namely how the Notary is responsible for authentic deeds made by or in front of him. The type of research used in this research is normative juridical, namely a research method that examines and analyzes secondary data. The research results show that authentic deeds as a Notary product have very strong legal force as evidence in court, therefore the preparation of authentic deeds must be accountable if there are errors in their writing. Thus, making an authentic deed must be accountable.